Neurodevelopmental effects of low dose ionizing radiation exposure: A systematic review of the epidemiological evidence. (March 2020) - Pasqual, Elisa; Bosch de Basea, Magda; López-Vicente, Mónica; Thierry-Chef, Isabelle; Cardis, Elisabeth
Highlights: We reviewed the evidence on possible neurodevelopmental effects of low-to-moderate doses of ionizing radiation. Selected studies were heterogeneous in terms of outcome and exposure assessment. The strength of evidence for an effect on general cognition and language was limited . The evidence for an effect on other neurodevelopment domains was inadequate . There was too little evidence to evaluate a possible difference in risk for exposure in utero compared to in childhood. Abstract: Background: The neurodevelopmental effects of high doses of ionizing radiation (IR) in children are well established. To what extent such effects exist at low-to-moderate doses is unclear. Considering the increasing exposure of the general population to low-to-moderate levels of IR, predominantly from diagnostic procedures, the study of these effects has become a priority for radiation protection. Objectives: We conducted a systematic review of the current evidence for possible effects of low-to-moderate IR doses received during gestation, childhood and adolescence on different domains of neurodevelopment. Data sources: Searches were performed in PubMed, Scopus, EMBASE and Psychinfo on the 6th of June 2017 and repeated in December 2018. Study eligibility criteria: We included studies evaluating the association between low-to-moderate IR doses received during gestation, childhood and adolescence, and neurodevelopmental functions. Study appraisal and synthesis methods: Studies were evaluated using the Cochrane Collaboration′s risk of bias tool adapted to environmental sciences. A qualitative synthesis was performed. Results: A total of 26 manuscripts were finally selected. Populations analyzed in these publications were exposed to the following sources of IR: atomic bomb (Hiroshima and Nagasaki), diagnostic/therapeutic radiation, and Chernobyl and nuclear weapon testing fallout. There was limited evidence for an association between low-to-moderate doses of IR and a decrease in general cognition and language abilities, that is, a causal interpretation is credible, but chance or confounding cannot not be ruled out with reasonable confidence. Evidence for a possible stronger effect when exposure occurred early in life, in particular, during the fetal period, was inadequate . Evidence for an association between IR and other specific domains, including attention, executive function, memory, processing speed, visual-spatial abilities, motor and socio-emotional development, was inadequate, due to the very limited number of studies found. Limitations, conclusions, and implications of key findings: Overall, depending on the domain, there was limited to inadequate evidence for an effect of low-to-moderate IR doses on neurodevelopment. Heterogeneity across studies in terms of outcome and exposure assessment hampered any quantitative synthesis and any stronger conclusion. Future research with adequate dosimetry and covering a range of specific neurodevelopmental outcomes would likely contribute to improve the body of evidence. Systematic review registration number: The systematic review protocol was registered in PROSPERO (registration number CRD42018091902).